Organizational learning II : theory, method and practice - Argyris, Chris (Addison-Wesley Pub. ReadingUS, 1996)
Identifies three types of productive organizational learning. Discusses factors which facilitate or inhibit productive organizational learning, and suggests how the inhibiting factors can be corrected. Demonstrates how the research and practice of organizational learning can be incorporated in today's business environment.